STOP, THAT and One Hundred Other Sleep Scales - Shahid, Azmeh; Wilkinson, Kate; Marcu, Shai; Shapiro, Colin M. (Springer New York : Imprint: Springer, 2012)
STOP, THAT and One Hundred Other Sleep Scales represents a unique, practical addition to the literature in sleep medicine.  There are at least four reasons why a sleep clinician should be familiar with rating scales that evaluate different facets of sleep.  First, the use of scales facilitates a quick and accurate assessment of a complex clinical problem.  In three or four minutes (the time to review ten standard scales), a clinician can come to a broad understanding of the patient in question. For example, a selection of scales might indicate that an individual is sleepy but not fatigued; lacking alertness with no insomnia; presenting with no symptoms of narcolepsy or restless legs but showing clear features of apnea; exhibiting depression and a history of significant alcohol problems.  Second, rating scales can provide a clinician with an enhanced vocabulary or language, improving his or her understanding of each patient.  In the case of the sleep specialist, a scale can help him to distinguish fatigue from sleepiness in a patient, or elucidate the differences between sleepiness and alertness (which is not merely the inverse of the former).   Scales provide clinicians with a repertoire of questions, allowing them to draw upon the extensive experience of their colleagues when attempting to tease apart nuanced problems.   Third, some scales are helpful for tracking a patient's progress.  A particular patient may not remember how alert he felt on a series of different stimulant medications. Scale assessments administered periodically over the course of treatment provide an objective record of the intervention, allowing the clinician to examine and possibly reassess her approach to the patient.  Finally, for individuals conducting a double-blind crossover trial or a straightforward clinical practice audit, those who are interested in research will find that their own clinics become a source of great discovery. Scales provide standardized measures that allow colleagues across cities and countries to coordinate their practices. They enable the replication of previous studies and facilitate the organization and dissemination of new research in a way that is accessible and rapid. The majority of STOP, THAT and One Hundred Other Sleep Scales is devoted to briefly discussing individual scales. When possible, an example of the scale is provided so that readers may gain a sense of the instrument's content.  Groundbreaking and the first of its kind to conceptualize and organize the essential scales used in sleep medicine, STOP, THAT and One Hundred Other Sleep Scales is  an invaluable resource for all clinicians and  researchers interested in sleep disorders.                .